Pengaruh Karakteristik Rumah Tangga dan Kewilayahan terhadap Kepemilikan Akta Kelahiran pada Rumah Tangga dengan Anak Umur 0-4 Tahun di Kawasan Timur Indonesia Tahun 2024 - -, Muhammad; Arcana, I Made (Politeknik Statistika STIS, 2025)
The coverage of birth certificate ownership among children aged 0–4 years in Eastern Indonesia (KTI) in 2024 is 78.29 percent, which has not yet reached the 2024 RPJMN target of 100 percent and is projected to remain below the Sustainable Development Goals (SDGs) target by 2030. This study aims to provide an overview of birth certificate ownership among households with children aged 0–4 years in KTI in 2024 and to analyze household and regional characteristics that influence birth certificate ownership. The data used is from the March 2024 Susenas and is analyzed both descriptively and inferentially using multilevel binary logistic regression. The results show that 80.83 percent of households with children aged 0–4 years in KTI possess a birth certificate. Households living in urban areas, with heads of household who have at least a primary education, are non-poor, have internet access, and are located in regions with higher average years of schooling and a higher percentage of births occurring in health facilities are more likely to own a birth certificate.